2021
DOI: 10.1002/ehf2.13682
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of haemodynamic response to muscle reflex in heart failure with reduced vs. preserved ejection fraction

Abstract: Aims Isometric handgrip (IHG) training reduces the blood pressure in patients with hypertension. It is unclear how IHG exercise affects the haemodynamics and cardiovascular function through the muscle reflex in patients with heart failure (HF) with reduced (HFrEF) and preserved ejection fraction (HFpEF). Methods and results Twenty patients (HFrEF: n = 10, HFpEF: n = 10) underwent left ventricular (LV) pressure-volume assessments using a conductance catheter and microtip manometer to evaluate haemodynamics, LV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Conversely, in patients with HFrEF, Notarius et al ( 37 ) reported significantly higher ΔBP than non-HF controls in a 2-min bout of 30% MVC static handgrip exercise, despite similar resting BP between groups. Further, Moriwaki et al ( 27 ) compared patients with HFpEF and HFrEF during 30% MVC static handgrip, finding that mean BP during exercise had no significant difference between groups despite patients with HFpEF exhibiting higher mean BP at rest, suggesting that the pressor responses to static exercise are smaller in patients with HFpEF than HFrEF. Together, unlike patients with HFrEF, individuals with HFpEF exhibit smaller BP responses during small muscle mass, static exercise compared to non-HF controls.…”
Section: Hemodynamicsmentioning
confidence: 99%
“…Conversely, in patients with HFrEF, Notarius et al ( 37 ) reported significantly higher ΔBP than non-HF controls in a 2-min bout of 30% MVC static handgrip exercise, despite similar resting BP between groups. Further, Moriwaki et al ( 27 ) compared patients with HFpEF and HFrEF during 30% MVC static handgrip, finding that mean BP during exercise had no significant difference between groups despite patients with HFpEF exhibiting higher mean BP at rest, suggesting that the pressor responses to static exercise are smaller in patients with HFpEF than HFrEF. Together, unlike patients with HFrEF, individuals with HFpEF exhibit smaller BP responses during small muscle mass, static exercise compared to non-HF controls.…”
Section: Hemodynamicsmentioning
confidence: 99%